Study guides

☆☆

Q: X plus 3y equals 7 x - 3y equals 1?

Write your answer...

Submit

Still have questions?

Related questions

(5, 1)

-3y + 6 = 7 Therefore, -3y = 1 Therefore, y = 1/-3 Therefore, y = -0.3 recurring (that is, -0.3333...)

5y+14+y = 3y-7 5y+y-3y = -7-14 3y = -21 y = -7

X equals 1 and so does Y

3y plus 7 makes a tomato pie and 1-y is .....em.......oh look at that it is past my bedtime! Cheerio!

The ordered pair is (-1, -7).

are you talking about a system of equations where x+3y=-7 -x+2y=-8 if so, then the answer is {2,-3}

{-4,-5}

7

If: -x-3y = -4 and 3x+5y = 16 Then: x = 7 and y = -1

x-y = 6 -x-3y = 22 -4y = 28 y = -7 So by substituting: x = -1 and y = -7

(Take 3y from both sides)3.2y + 7 = -1(Take 7 from both sides)3.2y = -8(Divide both sides by 3.2)y = -2.5

4y + 7 - y = 10 + 3y My next step is to combine the y's on the left, 3y + 7 = 10 + 3y If I then subtract 3y from both sides I obtain 7 = 10 which is not a true statement. Hence, the equation that you presented is invalid.

4x + 3y = 7 y = [(-4)/3] x + 7/3

x + 8y = 3 therefore 2x + 16y = 6 (a) 2x + 3y = -7 (b) Subtract (b) from (a): 13y = 13 so y = 1 and x = -5

x=2 y=7 5x+3y= 5 7 x 2 x 3 ____ _____ 10 21 21 + 10 _______ 31

x = 2 and y =1 so the lines intersect at (2, 1)

You need to organise your question properly. 3x+2y=4 4x + 3y= 7? Is 4 4x = 44x or 4-4x or 4+4x How can there be 2 equal signs in 1 equation?

given is that 4x+3y=6(3x+3y)=7 i.e., 6(3x+3y)=7 &&& 4x+3y=7 ---------------(1) 3x+3y=7/6 x+y=7/18 _________(2) multiply eqn(2) by 4 4x+4y=28/18 -------------------------(3) (3)-(1) 4x+3y-4x-4y=7-(28/18) y= -98/18 substitute y in eqn(2) x-98/18=7/18 x=7/18+98/18 x=105/18. therefore x=105/18 : y= -98/18

(y - 1)(3y + 7)

4y + 7 = 3y + 9-3y-7 -3y-7y = 24(2) + 7 = 3(2) + 98 + 7 = 6 + 915 = 15

7 + 8y - 3y + 2 =7 + 2 + 8y - 3y = 9 + 8y - 3y = 9 + 5y

(1) x+y=15(2) 4x+3y=38From (1) one gets x=15 -y, put into(2)4(15-y)+3y=3860-4y+3y=3860-y=38y=22 then x=15-y=-7(-7,22) is the solution

4y + 7 < 3y + 9 4y - 3y < 9 - 7 y < 2

16x2 + 8x + 1 - 9y2 = (4x + 1)2 - (3y)2 which is a difference of two squares. = (4x + 1 + 3y)*(4x + 1 - 3y)